A Web Experiment Showing Negative Effects of Slider Scales Compared to Visual Analogue Scales and Radio Button Scales. (April 2016) - Funke, Frederik
This article provides evidence that there is a substantial difference between slider scales and visual analogue scales (VAS), two types of rating scales used in web surveys that are frequently mixed up. In an experimental design, both scales were compared to standard HTML radio buttons and offered three, five, or seven response options. Slider scales negatively affect response rate (especially on mobile devices), the sample composition, the distribution of values, and also increase response times. VAS and radio buttons, however, can be used without negative side effects, even on touch screen devices like smartphones. Overall, it is recommended to avoid slider scales. As small differences in rating scales—here drag and drop versus point and click—have a huge influence on data collection, an optimal implementation of VAS is suggested. However, measurement of discrete variables with a moderate number of response options should be done with radio buttons scales unless a small screen size—for example, on smartphones—requires an economical use of space.